2009
DOI: 10.1152/ajpregu.00878.2007
|View full text |Cite
|
Sign up to set email alerts
|

Fourth ventricular administration of ghrelin induces relaxation of the proximal stomach in the rat

Abstract: appetite; vagus; fundus; stomach; medulla GHRELIN IS A RECENTLY IDENTIFIED endogenous ligand for growth hormone secretagogue receptor (GHS-R) and was originally isolated from the stomach (19). In addition to GH-releasing activity, ghrelin has an orexigenic (appetite-enhancing) effect. This is very reasonable, since the blood ghrelin level rose sharply just before onset of the dark phase, and the stomach ghrelin level was high during fasting in rats (30). Ghrelin has been shown to be present not only in the sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 35 publications
0
28
0
Order By: Relevance
“…To test this hypothesis, we used a selective GHSR antagonist [D-lys 3 ]-GHRP-6 to abolish the actions of ghrelin. We adopted a 37.5-fold dose of ghrelin administered which was shown to effectively blockage the GHSR-1a [22]. In our study, [D-lys 3 ]-GHRP-6 disabled the effects of ghrelin, indicating that ghrelin exerted a protective effect on barrier dysfunction through the GHSR-1a pathway.…”
Section: Discussionmentioning
confidence: 96%
“…To test this hypothesis, we used a selective GHSR antagonist [D-lys 3 ]-GHRP-6 to abolish the actions of ghrelin. We adopted a 37.5-fold dose of ghrelin administered which was shown to effectively blockage the GHSR-1a [22]. In our study, [D-lys 3 ]-GHRP-6 disabled the effects of ghrelin, indicating that ghrelin exerted a protective effect on barrier dysfunction through the GHSR-1a pathway.…”
Section: Discussionmentioning
confidence: 96%
“…In this study, the previously reported dosage of 100 g/kg body wt of desacyl ghrelin injected twice daily was adopted (33,38). We adopted a dosage of 3.75 mg/kg [D-Lys3]-GHRP-6 (37.5-fold dose of desacyl ghrelin), which was shown to effectively abolish the ghrelin-GHSR signaling (25). Mice in the DOX ϩ DAG ϩ [D-Lys3]-GHRP-6 group were administrated with [D-Lys3]-GHRP-6 immediately before desacyl ghrelin injection.…”
Section: Animalsmentioning
confidence: 99%
“…Ghrelin secretion exerts profound stimulatory effects upon gastric motility and acid secretion as well as food intake and energy metabolism 610 . This stimulatory effect has been demonstrated in both fed and fasted states 11,12 .…”
mentioning
confidence: 99%